Ecophysiological Responses of Two Olive Tree Cultivars (Olea europaea L. CV Koroneiki and Chemlali) Under Three Water Treatments - Hassine, Mortadha Ben; Boussadia, Olfa; Bchir, Amani; Moula, Ines; Hafi, Mariem El; Braham, Mohamed (European Scientific Journal, ESJ, 2017)
In this paper, our objective is to assess and compare the effects of three levels of irrigation application on the ecophysiological behavior and plant dry matter accumulation of two young olive tree cultivars Koroneiki, a promising greek cultivar, and Chemlali, the best local cultivar. According to this assessment, we can determine the most efficient water treatment that could be suitable for Mediterranean environments subjected to water shortage conditions. Measurements were made in the green house of the Tunisian Olive tree Institute under normal day-light conditions from March, 16th to April, 21st 2015. Three water treatments were applied which are T100% (control treatment: Daily irrigation at 100% of Available Water Content (AWC)), T50% (Daily irrigation at 50% of AWC) and T0% (Without watering). The results showed that the two olive tree cultivars possess important mechanisms to overtake limited water resources. However, some striking variations existed between the two cultivars studied. Indeed, as water stress increased (T0%), Chemlali maintained longer a high midday leaf water potential compared (- 4.54 MPa) to Koroneiki (- 5.8 MPa). T50% treatment seems to be sufficient for both cultivars. Measurements of total Osmotic Adjustment (OA) showed that olive trees use this mechanism to create very negative leaf water potentials in order to be able to extract water from a dry root environment. The root/shoot ratio of Chemlali plants at T50% treatment was the highest (1.08) comparatively with the other two treatments (0.70 and 0.79 for T100% and T0% AWC water treatments, respectively). This result shows that Chemlali plants valorize low quantities of water (T50%) rather than high quantities (T100%) and Koroneiki plants behave better when it is irrigated at 100% AWC. To conclude, Chemlali plants irrigated at 50% AWC, compared to Koroneiki plants, are the most suitable to tolerate water restriction conditions.